2021
DOI: 10.21608/ajdsm.2021.72936.1197
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory response of pulp tissue after different direct pulp capping materials at different storage time

Abstract: Objective: Evaluate histologically and compare the inflammatory pulp response following direct pulp capping of mechanically exposed dogs' teeth with: Ca(OH)2 base Dycal, UltraBlend Plus and TheraCal LC, at different time intervals. Subjects and methods. A total of 54 permanent teeth of six healthy dogs were used. They were randomly divided into three groups (n=18) according to pulp capping material used. Group I: Dycal, Group II: UltraBlend Plus (UBP) and Group III: TheraCal LC. All cavities were restored with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(28 reference statements)
1
0
0
Order By: Relevance
“…25 This makes scientists state that subsiding of the pulp inflammation by capping materials indicates their better biocompatibility for DPC. 26 DPC of immature dogs' teeth with MTA and KNO 3 /PCA in our study showed the formation of granulation tissue at the three time intervals. Granulation tissue is formed from fibroblasts and small blood vessels.…”
Section: Discussionsupporting
confidence: 56%
“…25 This makes scientists state that subsiding of the pulp inflammation by capping materials indicates their better biocompatibility for DPC. 26 DPC of immature dogs' teeth with MTA and KNO 3 /PCA in our study showed the formation of granulation tissue at the three time intervals. Granulation tissue is formed from fibroblasts and small blood vessels.…”
Section: Discussionsupporting
confidence: 56%